Toward a System of Evidence for All: Current Practices and Future Opportunities in 37 Randomized Trials. (April 2021) - Tipton, Elizabeth; Spybrook, Jessaca; Fitzgerald, Kaitlyn G.; Wang, Qian; Davidson, Caryn
As a result of the evidence-based decision-making movement, the number of randomized trials evaluating educational programs and curricula has increased dramatically over the past 20 years. Policy makers and practitioners are encouraged to use the results of these trials to inform their decision making in schools and school districts. At the same time, however, little is known about the schools taking part in these randomized trials, both regarding how and why they were recruited and how they compare to populations in need of research. In this article, we report on a study of 37 cluster randomized trials funded by the Institute of Education Sciences between 2011 and 2015. Principal investigators of these grants were interviewed regarding the recruitment process and practices. Additionally, data on the schools included in 34 of these studies were analyzed to determine the general demographics of schools included in funded research, as well as how these samples compare to important policy relevant populations. We show that the types of schools included in research differ in a variety of ways from these populations. Large schools from large school districts in urban areas were overrepresented, whereas schools from small school districts in rural areas and towns are underrepresented. The article concludes with a discussion of how recruitment practices might be improved in order to meet the goals of the evidence-based decision-making movement.